Kraški izviri v Sloveniji - analiza trendov - Jelen, Maja (Acta hydrotechnica, 2020)
Karst springs and aquifers are important sources of drinking water, so knowledge about the dynamics of changes in the hydrological characteristics of karst springs is especially important. This paper presents a hydrological trend analysis conducted for 14 karst springs in Slovenia. The trends of low, mean, and high annual flows were analyzed for the period from 1961 to 2013. Additionally, changes in annual rainfall, air temperature, and water temperature were investigated. The relationship between precipitation and discharges was also examined, as well as that between water and air temperature. Results indicate that low and mean flows in the selected springs are decreasing. In the case of high flows, no significant decreasing or increasing trend could be detected. For air temperature, the trend results were positive and statistically significant with the selected significance level. Some precipitation stations showed a significant decrease in the annual rainfall. Because the relationship between annual precipitation and mean flows is relatively high, the rainfall decrease could be the main reason for the decrease in low and mean flows. Moreover, the retention times of karst springs are relatively short. Some of the investigated springs are located in the Mediterranean part of the country where issues with drinking water supply occur commonly in the summer. If a similar dynamic continues, water scarcity problems can be expected in the future. The climate change models also predict such dynamics
Keywords: discharge; hidrologija; hydrology; karst springs; kraški izviri; Mann-Kendall test; pretoki; Slovenia; Slovenija; trendi; trends; vodarstvo in okoljsko inženirstvo